การเปรียบเทียบค่าความร้อนของก้อนเชื้อเพลิงจากส่วนผสมของถ่านกะลามะพร้าวและก้อนเห็ดหลังการเก็บผลผลิต A COMPARISON OF HEATING VALUE OF FUEL BRIQUETTE FROM THE MIXTURE OF COCONUT SHELL CHARCOAL AND MUSHROOM CUBE AFTER - ทับทิม, สุกัญญา; ปรือทอง, ศศิธร (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The present research article aims to produce fuel briquette and find the different ratios of heating value of fuel briquette from the mixture of coconut shell charcoal and mushroom cube after harvesting. The fuel briquette was produced in various mixing ratio of coconut shell charcoal and mushroom cube after harvesting. The ratios were 0:10, 1:9, 2:8, 5:5, 8:2, 9:1 and 10:0 and mixed with cassava glue. After pressing fuel briquette in cylindrical shape, dry them in the sun. The fuel briquettes were measured and finding the density, moisture content, the heating value and performance testing. The research finding revealed that the optimal proportion ratio of the mixture of coconut shell charcoal and mushroom cube after harvest were 8:2 and 9:1 which provided the density of fuel briquette at 584.14 and 661.10 kg/m3. The moisture content was 2.17 and 2.08% db. The heating value was 5,695.76 and 6,448.61 kcal/kg. The burning time was 210.12 and 198.98 min/kg. The ash was 3.32 and 6.68 %. The ratio of 8:2 and 9:1 had heating value higher than the heating value of the standard mark on the community product; the minimum heating value was 5,000 kcal/kg. Therefore, to produce the fuel briquette, the mixing ratio 8:2 and 9:1 of coconut shell charcoal and mushrooms cube after harvest were recommended for the community to increase value added from the agricultural wastes.